Comparison of sarcopenia and cachexia in men with chronic heart failure: results from the Studies Investigating Co‐morbidities Aggravating Heart Failure (SICA‐HF). (30th August 2018) - Emami, Amir; Saitoh, Masakazu; Valentova, Miroslava; Sandek, Anja; Evertz, Ruben; Ebner, Nicole; Loncar, Goran; Springer, Jochen; Doehner, Wolfram; Lainscak, Mitja; Hasenfuß, Gerd; Anker, Stefan D.; et al.
Abstract : Aims: Changes in heart failure (HF) patients' body composition may be associated with reduced exercise capacity. The aim of the present study was to determine the overlap in wasting syndromes in HF (cachexia and sarcopenia) and to compare their functional impact. Methods and results: We prospectively enrolled 207 ambulatory male patients with clinically stable chronic HF. All patients underwent a standardized protocol examining functional capacity, body composition, and quality of life (QoL). Cachexia was present in 39 (18.8%) of 207 patients, 14 of whom also fulfilled the characteristics of sarcopenia (sarcopenia + cachexia group, 6.7%), whereas 25 did not (cachectic HF group, 12.1%). Sarcopenia without cachexia was present in 30 patients (sarcopenic HF group, 14.4%). A total of 44 patients (21.3%) presented with sarcopenia; however, 138 patients showed no signs of wasting (no wasting group, 66%). Patients with sarcopenia had lower strength and exercise capacity than both the no wasting and the cachectic HF group. Handgrip strength, quadriceps strength, peak oxygen uptake (VO2 ), distance in the 6‐minute walk test (6MWT), and QoL results were lowest in the sarcopenia + cachexia group vs. the no wasting group ( P < 0.05 for all). Likewise, the sarcopenic HF group showed lower handgrip strength, quadriceps strength, 6MWT, peak VO2, and QoL results vs. the no wasting group ( P < 0.05 for all). Conclusion: Losing muscle with or without weight loss appears to have a more pronounced role than weight loss alone with regard to functional capacity and QoL among male patients with chronic HF. Clinical Trial Registration:ClinicalTrials.gov Identifier NCT01872299.